The Influence of Fiscal Policy on Gender-Specific Unemployment during the COVID-19 Shock in Poland - Al Mamun, Tuhin G. M. (Ekonomika, 2026)
The COVID-19 pandemic significantly disrupted labor markets worldwide, exacerbating pre-existing gender disparities in employment. This study examines the gender-specific impacts of the pandemic on unemployment trends in Poland from 1992 to 2023, by using a Markov Switching Vector Auto regression model. The results indicate that male unemployment rose more sharply than female unemployment during the initial shock, while female unemployment demonstrated a stronger recovery phase. Fiscal policy played a crucial role in shaping these trends, with government spending exhibiting a delayed but substantial effect in reducing unemployment, particularly in the second lag period. Optimized fiscal interventions suggest targeted policies can alleviate adverse economic effects. Together, these results emphasize the importance of gender-sensitive fiscal policies to support an equitable and resilient labor market recovery in Poland.
Keywords: COVID-19 pandemic; gender-specific unemployment; fiscal policy; Markov Switching VAR,; dynamic optimization